The effect of emotion regulation training on family relationships of hyperactive children - Zohre Arabi; Ladan Fattah Moghaddam; Mohammad Sahebalzamani (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: One of the psychiatric disorders related to childhood is attention deficit hyperactivity disorder that can negatively affect the family interactions of these children. Parents of these children, especially the mother as the main caregiver, need comprehensive training to make a positive difference in their attitudes and behaviors with these children. The purpose of this study was to investigate the effect of emotion regulation training on family relationships in hyperactive children. METHODS: This was a randomized clinical trial study with a control group performed on eighty mothers of hyperactive children who were selected randomly. The intervention group members attended emotion regulation skills training sessions for one session of 90 min each week for 8 weeks. During the training course in the intervention group, the control group did not receive any training. Data collection tools included demographic information questionnaires, Mother-Child Relationship Evaluation, and Rahim Organizational Conflict Inventory-II. Data analysis was performed by descriptive statistics and the analysis of covariance. RESULTS: The mean scores of the mother-child relationship in the intervention group showed a significant improvement in the subscales of acceptance, overprotection, facilitation, and rejection (P < 0.0001). The results of this research also showed improvements in all the five communication styles of integrating, avoiding, compromising, obliging (P < 0.0001), and dominating (P < 0.012) between spouses. CONCLUSION: It seems that the emotion regulation training approach in mothers with hyperactive children improved both the mother-child relationship and the interactive spousal styles and can be considered by the managers of treatment and rehabilitation field as an adjunctive therapy for the families of these children.